Bioprospecting and marine ‘omics’: surfing the deep blue sea for novel bioactive proteins and peptides - Moutinho Cabral, Inês; Gonçalves, Cátia; Grosso, Ana R.; Costa, Pedro M. (Frontiers in Marine Science, 2024)
The vast biological and biochemical diversity of the global ocean is the driver behind marine bioprospecting for novel bioproducts. As Marine Biotechnology is gaining momentum as one of the main pillars of the ‘Brue Growth’ revolution, the ability to screen for novel compounds of interest in species with little or no genomic resources is paramount. With this respect, proteins, which are easily metabolised, can be synthetised using convenient DNA recombinant methods and can easily be modified to better meet the needs of human society, making them prized targets. Evidently, proteins that hold natural bioactivity and specificity such as toxins and other venom components, have long captured the focus of biotechnologists, leading to the merger between environmental omics and toxinology termed as ‘venomics’. Indeed, bioactive proteins such as conopeptides, conotoxins, turripeptides and others are long deemed important subjects of research. Even though current mainstream paradigms set the focus on secondary metabolites from marine organisms, transcriptomics and proteomics approaches and their combination are rising strategies for screening for thousands of proteins and peptides in non-conventional biological models, emphasising, but not limited to, marine invertebrate animals due to their abundance, biodiversity and uncanny biochemical strategies to cope with selective pressure in literally every known marine habitat. Untargeted approaches, such as RNA-Seq – based transcriptomics and tandem mass spectrometry – based proteomics, can circumvent limitations related with absent or reduced genomic annotation. The present review will outline the main contributions of ‘omics’ and computational approaches for bioprospecting for proteinaceous marine bioactives. Despite the relatively low number of ‘omics’ studies with the main purpose of discover novel compounds, there is already important literature showcasing pipelines and approaches for revolutionising the exploration of the ocean.